‘I was lost in my life and they helped me find my way again’: Befriendee and befriender experiences of the Spirasi Befriending Programme for survivors of torture in Ireland - Hoare, Rachel (Torture Journal, 2023)
Introduction: Befriending is one of the rehabilitative services embedded in the holistic approach adopted by Spirasi, the Irish National Centre for the Rehabilitation of Survivors of Torture. Their befriending programme offers survivors one-to-one companionship from trained volunteer befrienders. The literature suggests that befriending programmes can improve quality of life, provide emotional support and combat loneliness. However, there is little empirical research of the effectiveness of befriending programmes for torture survivors. Objective: The main objective was to explore, in complementary ways, the impact of the Spirasi befriending programme on befrienders and befriendees and to incorporate their voices into recommendations for optimising the service. Methods: The methodology consisted of five focus groups (two with befriendees, two with befrienders and one with both) and a portrait workshop facilitated by two community artists, where each befriending pair member created a portrait of their partner to express and visually explore the befriending relationship. Data comprised the focus group transcripts and written feedback on the portrait-creation process. Results: The themes identified in both data sets firmly ground the befriending programme in Spirasi’s holistic approach to recovery. For the focus group participants, befriending promotes integration; models trusting, kind and reciprocal relationships; combats loneliness and protects against suicide. They also highlighted the importance of regular befriender training, increasing the programme’s reach and developing a befriender community of practice. The portrait workshop was found to strengthen relationships and provide a context of normality, acceptance and shared humanity through compassionate and creative exchanges. Conclusions: This paper highlights the benefits of the befriending programme within Spirasi’s holistic approach and the importance of collaborative expressive arts activities in building befriending relationships. It provides recommendations for good befriending practice which are relevant to all organisations working with survivors of torture as well as those working with people seeking international protection more broadly.